2005
DOI: 10.1111/j.1365-263x.2005.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

A study into dentists’ knowledge of the treatment of traumatic injuries to young permanent incisors

Abstract: Overall, the dentists' knowledge of the emergency treatment of dentoalveolar trauma in children was inadequate. Greater emphasis on undergraduate and postgraduate education in this area is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
69
5
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 17 publications
13
69
5
1
Order By: Relevance
“…From this case, we consider it necessary to adequately educate school and pool facility personnel regarding the immediate management of traumatic injuries, to stock preservative solution for avulsed teeth at places where trauma to teeth often occur, to establish a tie-up between such places and specialized dental clinics, and to improve the knowledge of both dentists and patients regarding management of traumatic injuries (13). Also, because surgical invasion was required in this case, it is essential to provide parents with sufficient information on the prognosis of teeth that experience trauma and importance of follow-up after replantation.…”
Section: Discussionmentioning
confidence: 99%
“…From this case, we consider it necessary to adequately educate school and pool facility personnel regarding the immediate management of traumatic injuries, to stock preservative solution for avulsed teeth at places where trauma to teeth often occur, to establish a tie-up between such places and specialized dental clinics, and to improve the knowledge of both dentists and patients regarding management of traumatic injuries (13). Also, because surgical invasion was required in this case, it is essential to provide parents with sufficient information on the prognosis of teeth that experience trauma and importance of follow-up after replantation.…”
Section: Discussionmentioning
confidence: 99%
“…This fi nding would appear to be corroborated by a number of previous studies which all have highlighted the lack of confi dence and competence in trauma management among UK dentists. [20][21][22] Indeed these previous papers have all called for an increase in trauma-related teaching within undergraduate and postgraduate dental curricula. The implications of poor trauma management are considerable with far-reaching economic, psychosocial and oral health consequences for the patient.…”
Section: Confi Dence In Relation To Trauma Managementmentioning
confidence: 99%
“…In Jackson's study of dentists in North East England, 36% had undertaken postgraduate training in dental trauma. The figure was higher in the Kostopolou study 10 , which was based on dentists in Yorkshire -47% had engaged in postgraduate training in dental trauma. Dentists in Yorkshire are likely to be able to access this training more easily because of the number of paediatric dentists working in the region and because of the significant publicity that was undertaken during a recent multi-centre randomised controlled trial on treatment for avulsed teeth, where the lead centre was in Leeds.…”
Section: Responsibility For Follow-up Carementioning
confidence: 98%
“…Shared care can reduce the burden on busy specialist services and/or on families who cannot easily access specialist care services -for example due to distance to travel to specialist centre Postgraduate training in dental trauma All respondents in Yorkshire were asked this question, and almost 40% (n=237) reported that they had engaged in postgraduate training in dental trauma at some stage since qualification. This question was not asked in the Welsh study, but was included in other surveys of dentists' experiences in dental trauma, 4,10 and thus it can be used as an indirect way of measuring the validity of the sample. In Jackson's study of dentists in North East England, 36% had undertaken postgraduate training in dental trauma.…”
Section: Responsibility For Follow-up Carementioning
confidence: 99%
See 1 more Smart Citation